Sobre Iván Olaya Peláez, Pilar González Bernaldo de Quirós, Jorge Márquez Valderrama (eds. académicos), Raza, eugenesia y políticas públicas en América Latina, 1900-1950 - Agostoni, Claudia (El Colegio de México, A.C., 2025)
-